PENGARUH STORE ATMOSPHERE DAN PERSEPSI HARGA TERHADAP MINAT BELI KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI PEMEDIASI (Studi Pada Warong Kobong di Kota Manado) - Bataha, Elza M.; Mananeke, Lisbeth; Ogi, Imelda W. J (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
Abstract : The research aims to review effect of Store Atmosphere and Price Perception On Consumer Buying Interest with Customer Satisfaction as a mediator on Warong Kobong in Manado. The population of the research were all customers in Warong Kobong. Sampling was carried out based on Issac Michael table 272 respondent and analysed with path analysis. The results showed that the Store Atmosphere have positive and significant impact on Consumer Buying Interest. Price Perception no significant on Consumer Buying Interest. Store Atmosphere and Price Perception have positive and significant on Consumer Satisfaction. Consumer Satisfaction have positive and significant on Consumer Buying Interest. Warong Kobong still must remain develop Price Perception to attract Consumer buying interest in Warong Kobong.Â Keywords: Store Atmosphere, Price Perception, Cunsomer Satisfaction, Consumer Buying Interest.